2017
DOI: 10.4088/pcc.16br02025
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine and “Z-Drug” Dependence

Abstract: High comorbidity occurs in this group of patients. Outcome varies significantly (P < .05) between sedative-dependent only and multiple-substance�dependent patients. High attrition should be addressed through follow-up and tracking mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In India, a retrospective study of 950 patients who were admitted from 2007 to 2014 in a tertiary addiction centre revealed that alprazolam (50.6%), nitrazepam (23.5%) and zolpidem (11.2%) were the most commonly reported drugs of abuse. 28 High misuse prevalence of benzodiazepines and Z-drugs in this study of patients with drug dependence may suggest that there are significant problems with the misuse of benzodiazepines and Z-drugs in India, which is similar to the findings of the UNODC report on prescription medicine misuse in South Asia. 13…”
Section: Prescription Medicine Misuse In Indiasupporting
confidence: 85%
“…In India, a retrospective study of 950 patients who were admitted from 2007 to 2014 in a tertiary addiction centre revealed that alprazolam (50.6%), nitrazepam (23.5%) and zolpidem (11.2%) were the most commonly reported drugs of abuse. 28 High misuse prevalence of benzodiazepines and Z-drugs in this study of patients with drug dependence may suggest that there are significant problems with the misuse of benzodiazepines and Z-drugs in India, which is similar to the findings of the UNODC report on prescription medicine misuse in South Asia. 13…”
Section: Prescription Medicine Misuse In Indiasupporting
confidence: 85%
“…The present study was a proof-of-concept comparison of LCA with PLA, applied to prescription claims data for 3 medications: alprazolam, the benzodiazepine with the greatest abuse liability; [ 14 , 15 ] opioids, which are a top public health concern because of an epidemic of misuse and overdose deaths; [ 1 , 16 ] and gabapentin, a noncontrolled substance recently identified as a medication of abuse [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 6307 patients who initiated benzodiazepine or Z-drug treatment, 3.5% used clonazepam or alprazolam, both of which are among the most common drugs of abuse worldwide. [31][32][33] Alprazolam has long been known for causing more severe physical dependence than other benzodiazepines, due to its high potency. 34 Similarly, warnings about the highly addictive properties of clonazepam have emerged in recent years, 35,36 indicating that the high rates of longterm use of these drugs may be due to patients becoming dependent.…”
Section: Discussionmentioning
confidence: 99%